Squamous Cell Carcinoma (Marjolin’s Ulcer) Arising in a Sacral Decubitus Ulcer Resulting in Humoral Hypercalcemia of Malignancy - John T. O’Malley; Candace Schoppe; Sameera Husain; Marc E. Grossman (Case Reports in Medicine)
Long-standing burns, fissures, and ulcers that undergo malignant transformation into a variety of malignancies, including squamous cell carcinoma, is commonly referred to as a Marjolin’s ulcer. It is well recognized that squamous cell carcinomas of the lung and esophagus can cause humoral hypercalcemia of malignancy secondary to paraneoplastic secretion of parathyroid hormone-related peptide. However, it is extremely rare for a squamous cell carcinoma developing in a sacral decubitus ulcer to cause humoral hypercalcemia of malignancy. We describe the first case of a patient found to have elevated serum levels of parathyroid hormone related peptide related to his Marjolin’s ulcer. A 45-year-old African American man with T6 paraplegia and a sacral decubitus ulcer present for 20 years was admitted for hypercalcemia of unclear etiology. He was subsequently found to have elevated parathyroid hormone related peptide and an excisional biopsy from the ulcer showed invasive squamous cell carcinoma suggestive of humoral hypercalcemia of malignancy. The patient ultimately succumbed to sepsis while receiving chemotherapy for his metastatic squamous cell carcinoma. Humoral hypercalcemia of malignancy is a rare and likely underrecognized complication that can occur in a Marjolin’s ulcer.